2020
DOI: 10.1103/physreva.102.012823
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic merged-ion-beam experiments in DESIREE: Final-state-resolved mutual neutralization of Li+ and D

Abstract: We have developed an experimental technique to study charge-and energy-flow processes in sub-eV collisions between oppositely charged, internally cold, ions of atoms, molecules, and clusters. Two ion beams are stored in separate rings of the cryogenic ion-beam storage facility DESIREE, and merged in a common straight section where a set of biased drift tubes is used to control the center-of-mass collision energy locally in fine steps. Here, we present measurements on mutual neutralization between Li + and D − … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…The increased relative velocity of the ions is found to correlate with a broadening of the r distributions. The same effect could be observed in other earlier experiments at DESIREE, 49,50 and is mainly attributed to the spread in the energies of the ion beams and a decreased accuracy in the approximation made in eqn (4). The metastable contribution (marked with an asterisk) remains present in both measurements.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The increased relative velocity of the ions is found to correlate with a broadening of the r distributions. The same effect could be observed in other earlier experiments at DESIREE, 49,50 and is mainly attributed to the spread in the energies of the ion beams and a decreased accuracy in the approximation made in eqn (4). The metastable contribution (marked with an asterisk) remains present in both measurements.…”
Section: Resultssupporting
confidence: 83%
“…Furthermore, the spread in the energies and velocity components of the ion beams results in broadening of the distributions. In recent MN studies at DESIREE by Eklund et al, 49,50 extensive Monte Carlo simulations were performed to take these effects into account. Given that these effects cannot be independently determined, here we instead chose to convolve the r distributions with Gaussians of adjustable width, in order to match the observed experimental broadening.…”
Section: Data Evaluationmentioning
confidence: 99%
“…They also obtained branching fractions for Li + +H − at E CM = 3 meV, which are in agreement with their Li + +D − values, though no error estimates are given. Eklund et al (2020) have with DESIREE obtained branching frac-tions into the 3s state for Li + +D − MN at E CM = 78, 262, and 630 meV. The 3p and 3d states are not resolved, but the measured 3s branching fraction (57.8±0.7 %) at 78 meV is the most precisely measured branching fraction value.…”
Section: Experimental Results and Comparison With Theorymentioning
confidence: 90%
“…total cross sections and branching fractions have been measured in Louvain (Launoy et al 2019), and branching fractions in Stockholm (Eklund et al 2020) at the DESIREE infrastructure (Thomas et al 2011;Schmidt et al 2013). Results for branching fractions have also been obtained for…”
Section: Measurements Of Mutual Neutralisation and Comparisons With A...mentioning
confidence: 99%
“…It was then found that the rate is a strong function of the rotational excitation, which is in stark contrast to what has been assumed in earlier astrophysical models. At DESIREE, the branching fraction for the population of the Li (3s) state-important for gauging the Li abundance in stars-was measured in Li + + D − mutual neutralization reactions [198] at meV energies. In the next step, reactions between small internally cold molecular anions and atomic cations present in the interstellar medium will be performed with improved methods to control the overlap between the merged beams in DESIREE.…”
Section: Challenges and New Directionsmentioning
confidence: 99%